2019
DOI: 10.5194/npg-2019-7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data assimilation as a deep learning tool to infer ODE representations of dynamical models

Abstract: Recent progress in machine learning has shown how to forecast and, to some extent, learn the dynamics of a model from its output, resorting in particular to neural networks and deep learning techniques. We will show how the same goal can be directly achieved using data assimilation techniques without leveraging on machine learning software libraries, with a view to high-dimensional models. The dynamics of a model are learned from its observation and an ordinary differential equation (ODE) representation of thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Some results are reported in a Supplementary Material document for the sake of brevity. This section focuses on the more challenging 3-dimensional Lorenz model (see in Lorenz, 1963) which is one of the favorite toy models in data assimilation since it is a sophisticated (nonlinear, non-periodic, chaotic) but low-dimensional dynamical system (Lguensat et al, 2017;Bocquet et al, 2019). The considered Lorenz-63 (L63) SSM on R 3 is defined as…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some results are reported in a Supplementary Material document for the sake of brevity. This section focuses on the more challenging 3-dimensional Lorenz model (see in Lorenz, 1963) which is one of the favorite toy models in data assimilation since it is a sophisticated (nonlinear, non-periodic, chaotic) but low-dimensional dynamical system (Lguensat et al, 2017;Bocquet et al, 2019). The considered Lorenz-63 (L63) SSM on R 3 is defined as…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Beskos et al, 2017) with advanced machine learning approaches for estimating m (see e.g. Bocquet et al, 2019;Fablet et al, 2017a) may allow to tackle higher dimensional problems with the additional advantage of leading to a reduction of computational costs if the machine learning tool is efficiently implemented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5.2.3. Data assimilation and ML Several studies have highlighted the connection between DA and ML [1,30,36,95]. The connection is more direct with 4DVar, in which a function that quantifies model-data disagreement (i.e.…”
Section: Model Errors and ML Within Data Assimilationmentioning
confidence: 99%
“…Recent advancements in machine learning technologies, particularly deep learning (DL) or deep neural networks, have largely impacted various industries due to precise image and speech recognition capability (Alam et al 2020;Yu et al 2020). Many meteorological studies based on DL have been conducted in recent years, including the discrimination of typhoon intensity (Pradhan et al 2018;Wimmers 2019;Daikoji et al 2020), precipitation nowcasting (Shi et al 2015;Samsi et al 2019;Agrawal et al 2019), quality check algorisms for observed values (Dai et al 2018), data assimilation (Bocquet et al 2019;Arcucci et al 2021), and subgrid parameterizations (Rasp et al 2018;Han et al 2020). However, only a few studies based on DL have been conducted on guidance for short-range weather forecasts (Scheuerer et al 2020;Veldkamp et al 2021), despite it has used machine learning techniques for approximately 50 years (Glahn and Lowry 1972).…”
Section: Introductionmentioning
confidence: 99%